Beyond open data: realising the health benefits of sharing data. (10th October 2016) - Pisani, Elizabeth; Aaby, Peter; Breugelmans, J Gabrielle; Carr, David; Groves, Trish; Helinski, Michelle; Kamuya, Dorcas; Kern, Steven; Littler, Katherine; Marsh, Vicki; Mboup, Souleymane; Merson, Laura; et al.
Abstract : Accessible data are not enough. We need to invest in systems that make the information useful, say Elizabeth Pisani and colleagues